Patients diagnosed with long QT syndrome after repair of congenital heart disease. Issue 11 (9th October 2018) - Song, Mi Kyoung; Bae, Eun Jung; Kim, Gi Beom; An, Hyo Soon; Ahn, Kyung Jin; Seong, Moon‐Woo; Park, Sung Sup
Abstract: Background: Patients with repaired congenital heart disease (CHD) can have both depolarization and repolarization abnormalities. A coexisting long QT syndrome (LQTS) may cause electrical instability in these patients; however, diagnosing LQTS is difficult owing to intraventricular conduction delay or paced rhythm after the operation. We report on six patients diagnosed with LQTS after CHD repair. Methods: We investigated two male and four female patients. Clinical data, electrocardiographic findings, and genetic analysis results were reviewed. Results: The range of patient age at LQTS diagnosis was 1.4‐22 years. There were two patients with tetralogy of Fallot, four with septal defect, and one with tricuspid atresia. All patients underwent total correction or a staged operation, without events. The diagnosis of LQTS was made in four asymptomatic patients and two symptomatic patients with recurrent syncope and ventricular fibrillation. During the postoperative follow‐up, their median QTc interval and QTc dispersion increased (from 474 and 41 ms preoperatively to 541 and 141 ms postoperatively, respectively; P = 0.043). T‐wave notching over three leads was observed in three patients. Genetic analysis showed SCN5A mutation in one, KCNH2 mutation in three, KCNQ1 mutation in one, and no identified mutation in one patient. An implantable cardioverter defibrillator was placed in two patients. Conclusion: A coexisting LQTS may confer additional risk for arrhythmia and sudden cardiac death in patients with CHD. Suspicion of LQTS and careful monitoring of the QT interval and T‐wave morphology are important during the follow‐up of patients with repaired CHD.